Декодування одновнмірннх циклічних М-послідовностей методом адаптивного сходження - Мельничук, С. І.; Таянов, С. А. (Видавництво Національного університету «Львівська політехніка», 2001)
The authors of the article have propounded a new method for decoding linear M-sequences. They have analyzed advantages and imperfections its software and hardware realization and developed decoding algorithms.